Association Between Nurses’ Compliance With Adult Early Warning Score Implementation and Inpatient Survival: A Cross-Sectional Study - Faizatiwahida, Novia; Hemu, Viky Noviani; Rondhianto, Rondhianto; Setioputro, Baskoro; Yunanto, Rismawan Adi; Haristiani, Ruris; Fadilah, Superzeki Zaidatul (Journal of Applied Nursing and Health, 2026)
Background: The adult Early Warning Score (EWS) is an essential instrument for early detection of a patient's deteriorating clinical condition. However, the effectiveness of EWS depends on nurses' compliance with its implementation. Non-compliance with EWS implementation can hinder early detection of patients' conditions and affect patient survival. This study aims to analyze the relationship between adult EWS implementation compliance and inpatient survival status. However, the evidence on the effect of compliance with EWS implementation on patient survival in real inpatient settings remains limited. This study aimed to examine the association between nurses’ compliance with adult EWS implementation and inpatient survival status. Methods: This study used an observational, cross-sectional design and was reported according to the STROBE guidelines. The research sample comprised 188 patients selected using a phased sampling technique (cluster sampling followed by simple random sampling). Data were obtained from the medical records of inpatients who met the inclusion and exclusion criteria. The independent variable in this study was compliance with the Early Warning System (EWS), while the dependent variable was the patient's survival status. Statistical analysis was carried out using Fisher's Exact test. Results: A total of 188 patients were analyzed, with 173 patients (92%) surviving and 15 patients (8%) dying. In the group that did not comply with the Early Warning System (EWS), there were 6 deaths (16.7%) and 30 patients survived (83.3%), while in the group that did comply with the Early Warning System (EWS), there were 9 deaths (5.9%) and 143 patients survived (94.1%). There was a significant association between EWS compliance and inpatient survival status (p = 0.044). Patients with EWS adherence had a higher chance of survival than non-compliant patients (OR = 3.18; 95% CI: 1.06–9.54). Conclusion: The implementation of EWS that is compliant plays an essential role in detecting early deterioration of patient conditions and improving patient survival and safety.